Transcriptional Analysis and Subcellular Protein Localization Reveal Specific Features of the Essential WalKR System in Staphylococcus aureus. - Olivier Poupel (PLoS ONE, 2016)
The WalKR two-component system, controlling cell wall metabolism, is highly conserved among Bacilli and essential for cell viability. In Staphylococcus aureus, walR and walK are followed by three genes of unknown function: walH, walI and walJ. Sequence analysis and transcript mapping revealed a unique genetic structure for this locus in S. aureus: the last gene of the locus, walJ, is transcribed independently, whereas transcription of the tetra-cistronic walRKHI operon occurred from two independent promoters located upstream from walR. Protein topology analysis and protein-protein interactions in E. coli as well as subcellular localization in S. aureus allowed us to show that WalH and WalI are membrane-bound proteins, which associate with WalK to form a complex at the cell division septum. While these interactions suggest that WalH and WalI play a role in activity of the WalKR regulatory pathway, deletion of walH and/or walI did not have a major effect on genes whose expression is strongly dependent on WalKR or on associated phenotypes. No effect of WalH or WalI was seen on tightly controlled WalKR regulon genes such as sle1 or saouhsc_00773, which encodes a CHAP-domain amidase. Of the genes encoding the two major S. aureus autolysins, AtlA and Sle1, only transcription of atlA was increased in the ΔwalH or ΔwalI mutants. Likewise, bacterial autolysis was not increased in the absence of WalH and/or WalI and biofilm formation was lowered rather than increased. Our results suggest that contrary to their major role as WalK inhibitors in B. subtilis, the WalH and WalI proteins have evolved a different function in S. aureus, where they are more accessory. A phylogenomic analysis shows a striking conservation of the 5 gene wal cluster along the evolutionary history of Bacilli, supporting the key importance of this signal transduction system, and indicating that the walH and walI genes were lost in the ancestor of Streptococcaceae, leading to their atypical 3 wal gene cluster, walRKJ.